A method and system for determining optimal G. - Harun, Harlisya; Ungku Chulan, Ungku Azmi Iskandar (2011)
The present invention relates to determining optimal G in communication system. The current approaches generate an exhaustive enumeration of generator matrix G to find the minimum determinant of each G. All the minimum determinants are compared with one another to find the maximum value of the minimum determinants. In effect, the entire process consumes a lot of time to complete. Optimally signature enhances the current process by calculating the optimal minimum determinant such that the maximum value of the minimal determinant is found before the search commences. Using the optimality signature, it is possible to predict the structural feature of optimal generator matrix G without the need to evaluate its minimal determinant. In effect the number of iteration is kept very low.